A Startling Case of Neonatal Hyperekplexia Responsive to Levetiracetam: A New Alternative in Management?. (November 2013) - Hussain, Shanawaz; Prasad, Manish; Rittey, Chris; Desurkar, Archanna
The authors report a case of hyperekplexia presenting in the neonatal period resistant to clonazepam that responded subsequently to levetiracetam. Hyperekplexia is often misdiagnosed as epilepsy and can be difficult to manage with a particular concern over neonatal apnea and an increased risk of sudden infant death syndrome. The mainstay of therapy to date has been with clonazepam. The authors describe the salient features of their case, clinical diagnosis, and issues pertaining to management. The authors believe this is the first reported case of the use of levetiracetam for effectively treating hyperekplexia within the neonatal and infant period.